Pengaruh Pengembangan Karier dan Budaya Kerja terhadap Loyalitas Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada PT Graha Sarana Duta Cabang STO Gambir - Farhan Saputra; Ganis Aliefiani Mulya Putri; Dita Puspitasari; Bayu Putra Danaya (Universitas 45 Surabaya, 2024)
The purpose of this study is to examine the impact of career development and work culture on employee loyalty with variable work productivity at PT Graha Sarana Duta STO Gambir Branch. Career development and work culture are exogenous variables in this study, whereas job productivity and employee loyalty are endogenous ones. The study included 114 employees from the PT Graha Sarana Duta STO Gambir Branch. The research sample size was set at 100 participants. In sampling, a simple random sample strategy was applied. To gather data for this study, a questionnaire technique was employed in the form of a Google form to get primary data, which would then be used as data to conduct out data analysis. External and internal measurement testing, as well as the use of the Structural Equation Model (SEM) - SmartPLS 3.0, were used to evaluate the hypothesis. This study yielded the following results: 1) Career development has a positive and significant effect on job satisfaction at PT Graha Sarana Duta STO Gambir Branch; 2) Work culture has a positive and significant effect on job satisfaction at PT Graha Sarana Duta STO Gambir Branch; 3) Career development has no effect and is not significant on employee loyalty at PT Graha Sarana Duta STO Gambir Branch; 4) Work culture has a positive and significant effect on employee loyalty at PT Graha Sarana Duta STO Gambir Branch; and 5) Job Satisfaction has a positive and significant effect on employee loyalty at PT Graha Sarana Duta STO Gambir Branch.